Impact of the COVID-19 Pandemic on the Intensity of Health Services Use in General Practice: A Retrospective Cohort Study - Yael Rachamin; Oliver Senn; Sven Streit; Julie Dubois; Michael J. Deml; Katharina Tabea Jungo; Katharina Tabea Jungo (Frontiers Media S.A., 2021)
Objectives: We aimed to explore the impact of the Swiss shutdown in spring 2020 on the intensity of health services use in general practice.Methods: Based on an electronic medical records database, we built one patient cohort each for January-June 2019 (control, 173,523 patients) and 2020 (179,086 patients). We used linear regression to model weekly consultation counts and blood pressure (BP) and glycated hemoglobin (HbA1c) measurement counts per 100 patients and predicted non-shutdown values. Analyses were repeated for selected at-risk groups and different age groups.Results: During the shutdown, weekly consultation counts were lower than predicted by −17.2% (total population), −16.5% (patients with hypertension), −17.5% (diabetes), −17.6% (cardiovascular disease), −15.7% (patients aged <60 years), −20.4% (60-80 years), and −14.5% (>80 years). Weekly BP counts were reduced by −35.3% (total population) and −35.0% (hypertension), and HbA1c counts by −33.2% (total population) and −29.8% (diabetes). p-values <0.001 for all reported estimates.Conclusion: Our results document consequential decreases in consultation counts and chronic disease monitoring during the shutdown. It is crucial that health systems remain able to meet non-COVID-19-related health care needs.